Influence of the physicochemical characteristics of pollutants on their uptake in moss. (February 2015) - Varela, Z.; Fernández, J.A.; Real, C.; Carballeira, A.; Aboal, J.R.
Abstract: Bryophytes are commonly used as biomonitors to estimate the atmospheric deposition of heavy metals and metalloids. However, the tissue concentrations of these elements in moss do not always accurately reflect atmospheric levels. The aim of the present study was to investigate whether element uptake in moss is affected by the physicochemical characteristics of the elements. Factor analysis was used to identify any patterns of covariance in the accumulation of elements in samples of the moss Pseudoscleropodium purum collected from the surroundings of different factories and from control sites. The variation in the concentrations of elements was similar in moss from both types of sites and was related to the binding properties of the elements. This suggests that the physicochemical characteristics of the elements determine the uptake of metals and metalloids from the atmosphere. Therefore, in studies that use multiple correlations among elements as indicators of a common origin of contaminants, erroneous conclusions may be reached by overlooking the adsorption properties of the moss. Highlights: Physicochemical characteristics of elements determine their uptake in moss. Factor analysis identifies groups depend on elements binding properties. Ionic and covalent nature of elements determines the radicals which they bind to.